The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/advs.201900038
|View full text |Cite|
|
Sign up to set email alerts
|

Definition of a Family of Nonmobile Colistin Resistance (NMCR‐1) Determinants Suggests Aquatic Reservoirs for MCR‐4

Abstract: Polymyxins, a family of cationic antimicrobial peptides, are recognized as a last‐resort clinical option used in the treatment of lethal infections with carbapenem‐resistant pathogens. A growing body of mobile colistin resistance (MCR) determinants renders colistin ineffective in the clinical and human sectors, posing a challenge to human health and food security. However, the origin and reservoir of the MCR family enzymes is poorly understood. Herein, a new family of nonmobile colistin resistance (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 90 publications
1
27
0
Order By: Relevance
“…Similar to previous studies ( Denervaud Tendon et al, 2017 ; Yang et al, 2017 ; Zhang et al, 2019 ), we found that the expression of mcr-1 was orchestrated and associated with an initial fitness cost (reduced growth at 8 h). However, to the best of our knowledge our study is the first to examine in any bacterial species the impact of the over-expression of the mcr-1 on bacterial metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies ( Denervaud Tendon et al, 2017 ; Yang et al, 2017 ; Zhang et al, 2019 ), we found that the expression of mcr-1 was orchestrated and associated with an initial fitness cost (reduced growth at 8 h). However, to the best of our knowledge our study is the first to examine in any bacterial species the impact of the over-expression of the mcr-1 on bacterial metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…MCR-3 was reported from Aeromonas species isolated from river water 32 . It has recently been reported that the aquatic bacteria of the genus Shewanella are a reservoir/progenitor for mcr-4 encoding gene 41 . MCR-5 and MCR-8 were described from the same Stenotrophomonas strain isolated from sewage water in China 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the United Nations Environment Programme (UNEP) recently identified environmental AMR as the top six emerging issues of concern [25,26]. In One Health model, surveillance of ARGs in humans, animals, soil, plant, aquatic and aquaculture environment is crucial in determining the extent of dissemination of a targeted ARG [2,27]. Potentially pathogenic COLROS emanating from any of these ecosystems can move with relative ease to another without barriers [2,25].…”
Section: Introductionmentioning
confidence: 99%